(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
In forensic practice, the identification of biological evidence, particularly blood traces, and the determination of their species affiliation is of significant diagnostic importance. Experience shows that identifying small, faint, long-stored, or altered blood traces resulting from external factors (washing, chemical exposure, contamination) often presents challenges when using traditional serological methods. Despite the widespread use of the precipitation reaction in a liquid medium, the Ouchterlony method, and immunoelectrophoresis, their sensitivity is not always sufficient. Therefore, there is a growing need for highly sensitive, specific, and simple-to-perform methods.